Macroeconomic Stability, Financial Inclusion, and Financial Literacy towards Economic Growth in Indonesia: Systematic Literature Review - Dewi, Dina Rizkia; Nugraha, Arindra Adhi; Wahyudi, Sugeng (LifeSciFi, 2024)
This article examines the influence of macroeconomic stability, financial inclusion, and financial literacy on Indonesia's economic growth, which is currently a major issue along with the increasing number of people who are entangled in online and illegal money loans, online gambling, and fraud that are financially detrimental. The purpose of this study is to see the influence of disturbed stability, including those caused by the above problems. This article uses a literature review method by reviewing several references sourced from previous studies that raise similar topics. Based on the sources that have been collected, reviewed, and analyzed, the results of this study found that financial stability is a significant factor in creating Indonesia's economic growth, especially in terms of financial inclusion and financial literacy. Based on the findings of this study, the government's role is needed in eradicating online gambling and illegal financial loan service providers and increasing the implementation of programs to improve the financial literacy of the Indonesian people. In addition, this study also suggests that financial inclusion should be promoted to maintain economic growth.